2008
DOI: 10.1002/term.106
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan microparticles as injectable scaffolds for tissue engineering

Abstract: The use of chitosan microparticles as injectable carriers for cell transplantation represents a promising alternative to avoid the drawbacks of the implantation of other forms of three-dimensional (3D) scaffolds seeded with cells. In this study, a 3D construct is obtained in vitro by combining chitosan microparticles crosslinked with genipin and goat bone marrow stromal cells (GBMCs). Cell viability and the morphology of GBMCs were evaluated after culture for 7 and 14 days. Our results show the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Our previous studies involving MSCs isolated from mice showed an increase in cell count over a period of 28 days, due to proliferation. Another recent study evaluated the in vitro cell viability and morphology in a 3D construct made by combining goat bone marrow stromal cells and CS MPs, which were crosslinked with genipin (García Cruz et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies involving MSCs isolated from mice showed an increase in cell count over a period of 28 days, due to proliferation. Another recent study evaluated the in vitro cell viability and morphology in a 3D construct made by combining goat bone marrow stromal cells and CS MPs, which were crosslinked with genipin (García Cruz et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan microparticles crosslinked with genipin and seeded with goat marrow stromal cells (GBMCs) in a 3D construct were shown to provide feasibility as injectable scaffolds after evaluation of cellular viability at 7 and 14 days in vitro , paving the way for injectable applications [25]. More recently, injectable microspheres have been demonstrated in vivo in rats.…”
Section: Types Of Bioactive 3d Structuresmentioning
confidence: 99%
“…CHT has been proved to be a biodegradable and biocompatible material and has been proposed for cartilage regeneration. Although many works demonstrated good biocompatibility of CHT scaffolds (García Cruz et al, ; Lao, Tan, Wang, & Gao, ; Lastra, Molinuevo, Blaszczyk‐Lezak, Mijangos, & Cortizo, ; Lastra, Molinuevo, Cortizo, & Cortizo, ), others have reported increased inflammatory response of CHT materials when macrophages were studied (Almeida et al, ; Bitencourt Cda, Silva, Pereira, Gelfuso, & Faccioli, ). This is why the possible inflammatory response was investigated using a model of RAW264.7 macrophages in culture in the presence of PLLA and/or CHT microspheres before implantation in animals.…”
Section: Introductionmentioning
confidence: 99%